Pengaruh Privacy (Security) Settings, Application Design dan E-Trust Terhadap E-Relationship Satisfaction Dan E-Loyalty Pada Konsumen Grabfood Di Surabaya - Sulistiyawati, Ucik (Universitas Yudharta Pasuruan, 2022)
English Version This study aims to explore the relationship between Privacy (Security) Settings, Application Design and E-trust towards e-relationship satisfaction and e-loyalty on Grabfood consumers in Surabaya. The study was conducted on 100 respondents who use the Grabfood application who are domiciled in Surabaya. After the analysis, the results show that there is an effect of privacy (security) settings on the e-trust of Grabfood application users in Surabaya. Privacy (security) settings have no effect on E-Relationship Satisfaction of Grabfood application users in Surabaya. Application design affects the e-trust of Grabfood application users in Surabaya. Application design affects the E-Relationship Satisfaction of Grabfood application users in Surabaya. E-trust has an effect on e-relationship satisfaction of Grabfood application users in Surabaya, but e-trust does not show a significant effect on e-loyalty of Grabfood application users in Surabaya. The results also show that e-relationship satisfaction has an effect on e-loyalty of Grabfood application users in Surabaya.Indo Version Tujuan penelitian ini adalah untuk menguji Pengaruh Privacy (Security) Settings, Application Design dan E-Trust Terhadap E-Relationship Satisfaction Dan E-Loyalty Pada Konsumen Grabfood Di Surabaya. Penelitian dilakukan kepada 100 responden pengguna aplikasi Grabfood yang berdomisili di Surabaya. Hasil penelitian ini adalah adanya pengaruh privacy (security) settings terhadap e-trust para pengguna aplikasi Grabfood di Surabaya. Privacy (security) settings tidak berpengaruh pada e-relationship satisfaction para pengguna aplikasi Grabfood di Surabaya. Application design berpengaruh pada e-Trust para pengguna aplikasi Grabfood di Surabaya. Application design berpengaruh pada e-relationship satisfaction para pengguna aplikasi Grabfood di Surabaya. E-trust berpengaruh pada e-relationship satisfaction para pengguna aplikasi Grabfood di Surabaya, namun e-trust tidak berpengaruh pada e-loyalty para pengguna aplikasi Grabfood di Surabaya. Hasil penelitian juga menunjukkan bahwa e- relationship satisfaction berpengaruh pada e-loyalty para pengguna aplikasi Grabfood di Surabaya.